Historia autyzmu od baśni i legend po badania genetyczne – laboratorium budowy mitów w nauce - Osóbka, Krzysztof (Biuletyn Historii Wychowania, 2017)
Autism is one of the most mysterious human disorders ever known. Although existing since the dawn of humanity, it was only in 1943 that science took up this subject. Before, undiscovered and unnamed, it was considered merely a legend, and the only existing records were those of a few pioneer case studies. With his discoveries, Leo Kanner, the first person to properly define autism, marked the beginning of a struggle to describe the disorder using scientific language. Unfortunately, the attempts were not always successful. Autism, as described by contemporary science, is a neurodevelopmental disorder. Theories claiming its psychogenic aetiology can no longer be sustained. The history of research concerning autism points to a phenomenon known as collective thinking – a term coined by Ludwik Fleck, as well as to the process of the emergence of a scientific myth. It is a study of how researchers’ presuppositions can shape social beliefs, and at the same time how constructing scientific theories is inherently ingrained in the cognitive style of an era. The second half of the 20th century marks the beginning of a gradual change in the classification of autism. The perception of the nature of this disorder shifted from psychogenic theories to organic aetiologies. It is the voice of the enormously talented and creative individuals with high-functioning autism that triggered a breakthrough in the research - a voice that was ignored until the 1980s.